The development of long-haul low-cost networks in the North Atlantic airline market: An exploratory data approach. (September 2020) - Zuidberg, Joost; de Wit, Jaap G.
Abstract: For almost two decades, discussion in the literature has continued regarding the viability of the long-haul low-cost carrier (LHLCC) business model in the North Atlantic market. From 2015 onward, LHLCC operations gained some steam, mainly due to the expansion of Norwegian's North Atlantic network. A detailed analysis of the traffic developments on the North Atlantic shows that LHLCCs have a tendency to operate on parallel routes while serving an aggregate North Atlantic network that is less seasonal than that of full-service network carriers (FSNCs). In addition, analysis of passenger flows shows that Norwegian's North Atlantic flights from its Scandinavian bases and, to a lesser extent, from London Gatwick carry substantial shares of transfer passengers. Furthermore, both in the North Atlantic market as a whole and in specific individual city pair markets there are signs that the entry of LHLCCs has a positive impact in terms of competition. Strategic responses by FSNC incumbents can be detected as well. For example, British Airways shows a larger increase in traffic (both in seats offered and in flight frequency) on routes contested by Norwegian than on North Atlantic routes not contested by Norwegian. Next to that, the British flag carrier is able to substantially undercut Norwegian's air fares on most of its contested routes. All in all, after more than a decade of EU-US and EU-Canada Open Skies agreements LHLCC operations on the North Atlantic are dominated by a single airline in financial dire straits. As a result, the long-term viability of the LHLCC business model on the North Atlantic is not a fait accompli yet. Highlights: Norwegian is fueling the growth of the LHLCC network on the North Atlantic. LHLCCs tend to operate on parallel routes with low aggregate seasonality. Indication that an increasing LHLCC market share on the North Atlantic drives competition. Signs of competitive responses of incumbent FSNCs in terms of traffic and pricing. The viability of the LHLCC business model on the North Atlantic remains questionable.